2007
DOI: 10.1093/nar/gkm094
|View full text |Cite
|
Sign up to set email alerts
|

Array-based profiling of reference-independent methylation status (aPRIMES) identifies frequent promoter methylation and consecutive downregulation of ZIC2 in pediatric medulloblastoma

Abstract: Existing microarray-based approaches for screening of DNA methylation are hampered by a number of shortcomings, such as the introduction of bias by DNA copy-number imbalances in the test genome and negligence of tissue-specific methylation patterns. We developed a method designated array-based profiling of reference-independent methylation status (aPRIMES) that allows the detection of direct methylation status rather than relative methylation. Array-PRIMES is based on the differential restriction and competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 48 publications
(54 reference statements)
0
33
0
Order By: Relevance
“…The first genome-wide approach to the MB (32) identified aberrant methylation affecting f6% and 1% of genes in MB cell lines and primary tumors respectively. Three additional genomewide studies have been published (29,30,33). Waha and colleagues (30) performed a differential methylation hybridization technique, from which they identified secretory granule neuroendocrine protein 1 (SGNE1/7B2) as a putative TSG that is methylated in MB.…”
Section: Discussionmentioning
confidence: 99%
“…The first genome-wide approach to the MB (32) identified aberrant methylation affecting f6% and 1% of genes in MB cell lines and primary tumors respectively. Three additional genomewide studies have been published (29,30,33). Waha and colleagues (30) performed a differential methylation hybridization technique, from which they identified secretory granule neuroendocrine protein 1 (SGNE1/7B2) as a putative TSG that is methylated in MB.…”
Section: Discussionmentioning
confidence: 99%
“…86 Epigenome-wide studies have identified different genes suppressed by DNA hypermethylation, such as ZIC2, COL1A2, and KLF4. 3,107,117 The work by Northcott et al 110 suggested that chromatin modifications contribute to medulloblastoma development. The authors described new amplifications and homozygous deletions targeting genes involved in histone lysine methylation, particularly H3K9: for example, amplifications of histone lysine demethylases (JMJD2C and JMJD2B), deletions of histone lysine methylatransferases (EHMT1 and SMYD4), and deletions in genes of the Polycomb group (L3MBTL2 and L3MBTL3).…”
Section: 85mentioning
confidence: 99%
“…Dopamine receptor D1 stimulates adenylyl cyclase and cyclic AMP-dependent protein kinases and regulates neuronal growth, development, and dopamine receptor D2-mediated events (Missale et al 1998). Up-regulated ZIC2 has been reported in invasive human tumors, such as lung cancers, endometrial cancers, pediatric medulloblastoma and synovial sarcoma (Gure et al 2000;Bidus et al 2006;PWster et al 2007;Fernebro et al 2006). In addition, ZIC2 antibody was isolated in sera obtained from patients with small cell lung cancer (Gure et al 2000;Sabater et al 2008;Vural et al 2005).…”
Section: Introductionmentioning
confidence: 99%